Significance of Ethnicity in the Risk of Acute Graft-versus-Host Disease and Leukemia Relapse after Unrelated Donor Hematopoietic Stem Cell Transplantation - Morishima, Yasuo (2013)
The significance of patient and donor ethnicity on risk of acute graft-versus-host disease (GVHD) and disease relapse after unrelated donor hematopoietic cell transplantation (HCT) is not known. A total of 4335 patient/donor pairs from the International Histocompatibility Working Group in HCT met the following three criteria: (1) HLA-A, B, C, DRB1 and DQB1 allele matched donor; (2) diagnosis of leukemia, and (3) non-T cell depleted GVHD prophylaxis. Post-transplant risks of acute GVHD and leukemia relapse were defined in Asian/Pacific Islander, Caucasian, African American, Hispanic, and Native American patients transplanted from donors with the same self-described background. Asian patients had a significantly lower incidence of acute GVHD (Japanese patients: 40.0% grades II-IV and 15.3% grades III-IV; non-Japanese Asian patients: 42.1% grades II-IV and 15.7% grades III-IV) compared to Caucasian patients (56.5% grades II-IV and 22.6% grades III-IV) (p< 0.001). The hazard ratio (HR) of acute GVHD for Caucasian patients was significantly higher than for Japanese patients. Unexpectedly, the HR of leukemia relapse in Caucasian patients with early disease status was also significantly higher than that in Japanese patients. These results provide a platform for future investigation into the genetic factors for unrelated donor HCT and clinical implications of diverse ethnic background.